Enhancing Money Laundering Investigation Through Analytic Maturity - Wido Lestari; Tubagus M. Yusuf Khudri (Yayasan Riset dan Pengembangan Intelektual, 2024)
Using Analytic Maturity Model (AMM) from the Organisation for Economic Co-operation and Development (OECD) (2022) framework, this study aims to examine the analytic capabilities of Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK) as Indonesia’s Financial Intelligence Unit (henceforth, FIU Indonesia) in using its resources and getting the most out of its internal and external data to produce financial intelligence reports used by law enforcement authorities to conduct money laundering investigations and/or its predicate offenses. OECD AMM consists of two perspectives: strategic and operational. Each perspective contains indicative attributes that assist in understanding what a given level of maturity means. These indicative attributes were assessed using in-depth interviews and/or results from focus group discussions as primary data and then validated using the triangulated method, with desk review as secondary data. This research found that FIU Indonesia has achieved level 3 out of 5 levels of analytic maturity based on OECD AMM from both strategic and operational perspectives. To encourage money laundering investigations, FIU Indonesia should improve the process of prioritizing cases by enhancing its analytical capabilities.